A comparative study on the clinical effectiveness of pumice with toothpaste and different prophylactic pastes in the removal of nicotine stains - Dujunco, Carla D.G.; Vallesteros, Manuel V.; Academia, Susan (Adviser).
Seventy-five patients having the lingual surfaces of their upper central incisors with nicotine stains extending from the cervical to the middle third of the tooth were polished with three different polishing agents. The right central incisor was polished with pumice with toothpaste while the left central incisor was polished with a prophylactic paste. The patients were divided into two groups- prophypaste was used for the first group, zircate for the second group, and ziroxide for the third group. Results showed that there is no significant difference in terms of polishing ability between pumice with toothpaste, ziroxide, zircate except prophypaste. To support the clinical findings, the particles of two polishing agents, pumice with toothpaste and zircate were viewed under the SEM. It was revealed that the particles of pumice are bigger, of greater diameter, producing a rougher surface compared to zircate which had finer particles, of smaller diameter, producing a smoother surface.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental care; Teeth -- Care and hygiene; Teeth -- Bleaching